Teore acuḿulo de nutrientes no consórcio de milho com forrageiras no sistema plantio direto - De Mendonc¸a, Veridiana Z. [UNESP]; De Mello, Luiz M. M. [UNESP]; Andreotti, Marcelo [UNESP]; Yano, Élcio H. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2014)
Aiming to evaluate the nutrient uptake of forage intercropped with maize (Zea mays), was conducted in the experimental area of the UNESP, campus of Ilha Solteira, in an study consisted of intercropping maize with four tropical forages: Urochloa brizantha, Urochloa ruziziensis, Megathyrsus maximus cv. Tanzania and Megathyrsus maximus cv. Aries, sown in three ways: 1) in the seeding row of maize, seeds mixed with fertilizer; 2) throwing in the day of sowing maize and 3) throwing in the V4 stage of maize. Randomized block designs with a 4 x 3 factorial design with four replicates were established. During the corn silage harvest samples were collected shoots of corn and forage. The plant material after oven dried, weighed and crushed for determination of macronutrients N, P, K, Ca, Mg and S. In forages, extraction of N, P and K was lower when the forage seeding was done by throwing the corn V4 stage and among the species studied; U. ruziziensis shows greater ability to extract soil nutrients when grown in a consortium. The corn crop had adequate nutritional contents and arrangement of intercropping did not affect the nutrient uptake of the crop regardless of the consortium.
Content and accumulation nutrient in the corn intercropped with forage in no tillage
Keywords: Cerrado; Crop-livestock integration; Interspecific competition; Plant nutrition